Implementación de un sistema de costos por órdenes de producción en la fábrica del mueble cantón Latacunga provincia de Cotopaxi, en el periodo enero-junio 2014 - Calero Silva, Lorena Belén (2016)
This research work is about the Implementation of a System Cost by manufacturing orders in “Fábrica del Mueble” Latacunga canton Cotopaxi province during January-June 2014 period; in which, it was determined that the main problem affecting its financial, economic and production activities was the lack of an adequate system of costs, empeding to know exactly real manufacturing costs. The descriptive method was used for this type of research obtaining the necessary information about activities of the company, by investigative techniques a interview was made to the company’s owner, the accountant and the production manager with the information obtained, it was determined that the system will allow to the factory to determine with greater accuracy and clarity the actual costs incurred in the production process....